Sequence and structure relationships within von Willebrand factor - Zhou, Yan-Feng (American Society of Hematology, 2012)
In the present study, we re-annotated von Willebrand factor (VWF), assigned its entire sequence to specific modules, and related these modules to structure using electron microscopy (EM). The D domains are assemblies of smaller modules visible as lobes in EM. Modules in the D-domain assemblies include von Willebrand D, 8-cysteine, trypsin inhibitor-like, E or fibronectin type 1-like domains, and a unique D4N module in D4. The D1-D2 prodomain shows 2 large connected assemblies, each containing smaller lobes. The previous B and C regions of VWF are re-annotated as 6 tandem von Willebrand C (VWC) and VWC-like domains. These 6 VWC domains correspond to 6 elongated domains that associate in pairs at acidic pH in the stem region of VWF dimeric bouquets. This correspondence is demonstrated by binding of integrin α(IIb)β(3) to the fourth module seen in EM, VWC4, which bears the VWF Arg-Gly-Asp motif. The C-terminal cystine knot domain dimerizes end-to-end in a manner predicted by homology to TGF-β and orients approximately perpendicular to the VWC domains in dimeric bouquets. Homologies of domains in VWF to domains in other proteins allow many disulfide bonds to be tentatively assigned, which may have functional implications.